GAMBARAN UMUM HASIL PEMERIKSAAN DARAH LENGKAP PADA PASIEN TERINFEKSI VIRUS DENGUE PRIMER DAN SEKUNDER DI RSUP SANGLAH DENPASAR - Arya Candra, I Kadek; Putu Sutirtayasa, I Wayan; Wiradewi Lestari, Anak Agung (E-Jurnal Medika Udayana; Vol 6 No 7 (2017): E-Jurnal Medika Udayana, 2023)
The diagnosis of primary or secondary Dengue virus infection is quite difficult because of the wide spectrum of symptoms and signs. Complete blood count testing  may be the initial screening to determine diagnosis and therapy accurately. This study aimed to determine the general description of the results of a complete blood count includes the number of platelets, leukocytes, hematocrit, and hemoglobin in patients with primary and secondary Dengue virus infection. This was a descriptive cross-sectional study by taking data from medical record retrospectively with total sampling methode. Samples were patients with primary and secondary Dengue virus infection listed on Sanglah Denpasar Hospital during July 2013 - June 2014. The variables were analyzed by SPSS for Windows. The total sample were 202 peoples (46 primary-infected patients and 156 secondary-infected patients). The proportion of primary-infected patients and secondary-infected patients who has platelet count ?47.750 x 10 3 /mL was 17.4% and 59.6%, the proportion of patients with leukocyte counts >3.965 x 10 3 /mL was 30.4% and 55.8%, the proportion of patients with hematocrit >45.04% was 41.3% and 55.1%, and the proportion of patients with a hemoglobin level of >15.3 g/dL was 39.1% and 51.9%. It can be concluded that the majority of secondary-infected patients had lower platelet counts, but has the leukocyte count, hematocrit, and hemoglobin higher than the primary-infected patients. However, further research is needed to determine the relationship between the variables.   Keywords: platelet, leukocyte, hematocrit, hemoglobin, primary and secondary Dengue virus infection.